Blends of epoxy resin with polycarbonate and CTBN rubber - Jayle, L. (Cranfield University, 1991)
The study described in this thesis examines how the toughenability of a difunctional epoxy resin cured with a diamine hardener is affected by the presence of a dissolved polycarbonate in the epoxy matrix, when that matrix is modified by CTBN rubber particles. The compatibility between the epoxy resin and four different polycarbonate types is investigated. Influence of polycarbonate content and of the type of polycarbonate upon the mechanical properties and morphology of polycarbonate or rubber-polycarbonate modified epoxy systems is considered. Toughenability of the epoxy matrix is found not to be improved by the presence of dissolved polycarbonate. Study of chemical interactions between polycarbonate and epoxy resin and polycarbonate and hardener shows a degradation of the polycarbonate by the epoxy resin and also by the diamine hardener. Failure of the polycarbonate to increase the toughenability of the epoxy matrix is considered to be related to this degradation. Toughness properties of polyethersulfone modified epoxy systems are also considered.